A simple solution for prefabricated vertical drain with surcharge preloading combined with vacuum consolidation. Issue 1 (February 2021) - Nguyen, Trong Nghia; Bergado, Dennes T.; Kikumoto, Mamoru; Dang, Phuoc H.; Chaiyaput, Salisa; Nguyen, Phu-Cuong
Abstract: Prefabricated vertical drains (PVDs) with the surcharge preloading and vacuum consolidation has become considerably popular for ground improvement projects. A simple solution that incorporates the fundamental embankment features, such as the average degree of consolidation and excess pore pressure, are essential for the design of soft ground improvements by PVDs with vacuum preloading. However, most of the solutions for vertical drains with vacuum consolidation require numerical simulations, whose implementation tends to be laborious. In contrast, a simple solution for vacuum consolidation under time-dependent loading has not yet been proposed. In this study, a simple solution that can be easily incorporated into a conventional spreadsheet is derived for PVDs with vacuum preloading by applying the Laplace transform technique. The proposed solution accounts for several actual construction conditions, such as initial surcharge load, vacuum pump trial period, variations of radial permeability, and time-dependent loading. The results obtained from this proposed approach were validated with those from the finite element method and field data from the case study of the Cai Mep International Terminal project in southern Vietnam. The derived solutions, including the excess pore pressures and average degrees of consolidation, were in good agreement with the predicted and observed data. Highlights: In this study, a simple solution that can be easily incorporated into a conventional spreadsheet is derived for PVDs with vacuum preloading by applying the Laplace transform technique. The proposed solution accounts for several actual construction conditions, such as initial surcharge load, vacuum pump trial period, variations of radial permeability, and time-dependent loading. The results of derived solutions by the proposed solution were in good agreement with the predicted results from finite element method and observed field data.